Class AB tunable active inductor. Issue 1 (1st January 2015) - Pantoli, L.; Stornelli, V.; Leuzzi, G.
Abstract : A class AB active inductor with high linearity, including a minimum number of components, is presented. Class AB operation is absent from the literature on the design of active inductors but is addressed in this reported work. Circuit details are given. A prototype board on a TLX8 substrate has been fabricated and tested showing the circuit feasibility for use in many commercial market applications, as integrated circuits, or discrete filters and oscillators.